Dyslipidemia among psychiatric patients with depression – common possible reasons and treatment implications – review - Pleska, Kacper; Wojtania, Joanna; Łepik, Michał; Uszok, Zofia; Rosiak, Krzysztof; Reguła, Kacper; Waloch, Kamil; Piaszczyński, Szymon; Czajka, Andrzej; Szymański, Bartłomiej (Quality in Sport, 2024)
Dyslipidemia is a medical term used to describe an abnormal level of lipids (fats) in the blood. This can include elevated levels of total cholesterol, low-density lipoprotein (LDL) cholesterol, high density protein lipoprotein (HDL) cholesterol and serum triglicerides. Depression, also known as depressive disorder, is a common mental illness. It is characterized by a persistent feeling of sadness, loss of pleasure, or lack of interest in activities that are present of at least two weeks and significantly impair patient everyday functioning. Dyslipidemia and depression can co-occur due to a complex interplay of shared risk factors, such as inflammation, metabolic syndrome, medication side effects, and lifestyle changes, suggesting a bidirectional relationship where each condition might contribute to the development or exacerbation of the other. Given these considerations, a comprehensive approach to managing dyslipidemia in psychiatric patients with depression is essential. This should include regular monitoring of lipid profiles and monitoring of anticholesterol and antidepressant drugs. Interestingly, simple lifestyle changes, such as a healthy diet and exercise, have an impact on the treatment of depression and dyslipidemia.